A STUDY OF THE RELATIONSHIP BETWEEN TEACHERS’ PERCEPTION OF ORGANIZATIONAL CULTURE AND PROFESSIONAL DEVELOPMENT IN CHAOZHOU No.2 HIGH SCHOOL, GUANGDONG PROVINCE, CHINA - LIN, ZHE; VINITWATANAKHUN, WATANA (Scholar: Human Sciences, 2022)
This study sought to determine the relationship between teachers’ perceptions of the organizational culture and professional development in Chaozhou No.2 High School, Guangdong province, china. To do so, the study evaluated the teachers’ perception of the organizational culture as well as their professional development in which Means and Standard Deviations were used for descriptive and quantitative analysis. Finally, the relationship between these two variables were analyzed and assessed through Pearson Product Moment Correlation Coefficient analysis. The basis for the organizational culture concept of this study was founded on Denison (1990)’s Theory. Moreover, Guskey (2003) ’ s Theory of Professional Development was the foundation to support the researcher’s concept of professional development. It was conducted in the academic year of 2020 – 2021and 80 full-time teachers responded to the questionnaire, while the response rate was 100 percent. This study focused on three objectives: (1) To determine the level of teachers’ perception toward organizational culture in Chaozhou No.2 high school, Guangdong Province, China. (2) To determine the level of teachers’ perception toward professional development in Chaozhou No.2 high school, Guangdong Province, China. (3) To determine the relationship between the level of teachers’ perception toward organizational culture and professional development in Chaozhou No.2 high school, Guangdong Province, China. Since Pearson correlation r is .645 and Sig. is .000, which is smaller than .05. The finding revealed that the teachers at Chaozhou No.2 high school had a relatively high perception towards the organizational culture and professional development.